Electronic structure and acid–base properties of Kojic acid and its dimers. A DFT and quantum topology study. (18th October 2017) - Aziz, Saadullah G.; Alyoubi, Abdulrahman O.; Elroby, Shaaban A.; Hilal, Rifaat H.
ABSTRACT: Kojic acid is a polyfunctional heterocyclic compound, with several important reaction centres; it has a wide range of applications in the cosmetic, medicine, food, agriculture and chemical industries. The present study aims at better insight into its electronic structure and bonding characteristics. Thus, density functional theory at the M06-2x /6-311++G ** level of theory is used to investigate its ground state electronic and acid–base properties. Protonation and deprotonation enthalpies are computed and analysed. The ability of Kojic acid to form both water complexes and dimers is explored. Several different complexes and dimer structures were examined. Natural bond order and quantum topology features of the charge density were analysed. The origin of the stability of the studied complexes and dimer structures can be traced to hydrogen bonding, π-conjugative and non-covalent dispersive interactions. Abstract :